Paraguay : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Paraguay. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation on Paraguay focused on the policies needed to promote long-term growth, widen the tax base, improve public spending efficiency, and strengthen financial sector supervision. Poverty has fallen sharply, from 58 percent in 2002 to 26 percent currently, although it remains one of the highest in Latin America. Continued convergence is expected to help reduce poverty further and help generate revenues to finance large spending needs. The banking sector is well-capitalized and stable, but the casas de credito and casas comerciales need to be better understood and supervised. The pension system needs reform, both to prevent large pension deficits in the future, and to boost the development of the domestic capital market for long-term instruments. The authorities concurred with IMF staff's assessment of the main bottlenecks to long-term economic growth. They also agreed structural reforms would help to attract more foreign investments and increase the dynamism of domestic private sector.